What are important consequences in children with non-specific spinal pain? A qualitative study of Danish children aged 9–12 years - Lise Hestbæk; Henrik Hein Lauridsen; Anna Bjellekjær Stolpe; Cornelius Myburgh (BMJ Open)
Objectives It is currently unknown whether children, adolescents and adults experiencing non-specific spinal pain are affected by their pain in a similar manner. It is also unclear whether questionnaires developed for adults can simply be transferred to paediatric populations. The objective of this study was to explore the physical, psychological and social consequences of a life with non-specific spinal pain among Danish children and to compare these consequences with the content of common adult questionnaires.Design and setting A qualitative study based on individual interviews and focus group discussions with participants recruited from two public schools in Denmark.Participants Thirty-six children aged 9–12 years with spinal pain were invited to an interview using a purposive sampling strategy with age, pain intensity and frequency, and general well-being status as inclusion criteria. Nineteen (9 girls, 10 boys) accepted to participate.Methods Data were transcribed verbatim and coded by following a thematic approach to elicit key concepts relevant to spinal pain. Subsequently, focus group interviews were conducted, and all codes were assigned categories corresponding to the International Classification of Function, Disability and Health (ICF) for comparison to adult questionnaires.Results Nineteen interviews were included, and 21 individual codes identified. Across the codes, five themes emerged in relation to children’s experiences of living with spinal pain: ‘Sports and play’, ‘Axial loading’, ‘Coping strategies’, ‘Mood changes’ and ‘Pain anxiety’. Codes and themes were elaborated on by the focus groups. Only approximately 40% of the identified ICF categories were covered by adult spinal questionnaires.Conclusions The negative impact of non-specific spinal pain on children aged 9–12 years pivots around codes which are considerably different to adults. Psychological and social factors were more prominent and pain anxiety was dominant in the lived lives of children. New questionnaires should be age specific and include the identified codes within each theme.